Peranan Lembaga Pemberdayaan Masyarakat (LPM) dalam Pembangunan di Kelurahan Santi Kecamatan Mpunda Kota Bima - Furkan Zulfikar Rahfani (Jurnal Hukum dan Sosial Politik, 2023)
The purpose of this study was to determine the role of the Kelurahan Community Empowerment Agency in coordinating development planning, the role of the Kelurahan Community Empowerment Agency in coordinating the planning of community institutions, and the role of the Kelurahan Community Empowerment Agency in planning development activities in a participatory manner in Santi Village, Bima City. This type of research is descriptive qualitative. Data collection techniques are interviews, observation, and documentation. Informants included the village head, village staff, LPM administrators, PKK administrators, Youth Organization administrators, Rukun Warga administrators, Rukun Tetangga, and residents who made arrangements in Santi Village. Determination of informants using purposive sampling technique. The analysis technique used is descriptive qualitative analysis, which starts from data reduction, data display, and verification and conclusion making. The research results obtained are: 1) with regard to coordinating development planning as the role of the Village Community Empowerment Institution, the results obtained have played a role and are in accordance with the mandate of Permendagri Number 5 of 2007 concerning Structuring Community Institutions and Government Regulation Number 73 of 2005 concerning Structuring Village Institutions. 2) With regard to coordinating the planning of community institutions as the role of the Kelurahan Community Empowerment Agency, the results obtained are as follows.